A ductile fracture model for AZ31B considering current parameters in electrically-assisted forming process. (November 2021) - Wang, Xinbao; Zhang, Haiming; Dong, Xianghuai
Highlights: The effect of pulse current on the damage evolution under different stress states was studied. A flow model suitable for electrically-assisted forming of AZ31B magnesium alloy was established. An analytical model accounting for the effect of effective current density, pulse frequency and stress state on fracture strain was presented. Abstract: In the forming process of magnesium alloy AZ31B, the pulse current can significantly lift the elongation and reduce the flow stress. Making use of this characteristic, electrically-assisted forming technology has gradually attracted the attention of industry and academia. However, the research regarding electro-plastic effect is not enough to direct the process design in practical production due to the lack of suitable fracture model. In this paper, a novel method to determine the fracture strain of AZ31B in the electrically-assisted forming process is investigated. In order to achieve this goal, series of experiments involving different stress states and electric pulse conditions are conducted to investigate the deformation and fracture behavior of AZ31B with and without electric pulses. Based on the experimental and corresponding simulation results, a ductile fracture model for AZ31B considering stress triaxiality, Lode parameter and current parameters is established, by modifying DF2015 fracture model. The proposed model is verified by specifically designed experiments with two types of specimens, the comparison suggests that the proposed model provide a satisfactory prediction of ductile fracture behavior of AZ31B.